Does Roadside Vegetation Affect Driving Performance?: Driving Simulator Study on the Effects of Trees on Drivers' Speed and Lateral Position. Issue 1 (January 2015) - Calvi, Alessandro
This study investigated the effects of roadside vegetation on driving performance on a two-lane rural road. In a driving simulation, 44 participants drove along seven roadside tree configurations. The configurations were characterized by two offsets of trees from the road edge (1.5 and 4.0 m) and three spacings between trees (10.0, 17.5, and 25.0 m) located on the roadside of a two-lane rural road that was 6.0 m wide. One additional configuration, without trees, was used as the baseline condition. The investigation was developed over five geometric elements: sharp left curve, sharp right curve, gentle left curve, gentle right curve, and tangent. Compared with the baseline condition, when trees were close to the road edge, drivers were found to decrease their speed significantly and move toward the centerline of the road. By contrast, when the offset of trees was increased, drivers adopted higher speeds that increased the distance from the road edge but with a lower left lateral displacement. This occurred along all five geometries, especially on sharp curves. Tree spacing did not affect the drivers' speed but significantly influenced the lateral position: drivers moved farther away from the road edge when tree spacing was decreased. The results demonstrated that drivers balanced the useful guidance information that roadside trees provided with the risk associated with the presence of trees: when trees were far away, the sense of guidance was predominant, and drivers adopted higher speeds; when trees were closer, drivers saw the trees as a risk, slowed down, and moved further away from them. Such driving behavior has direct impacts on the safety implications of roadside trees.